(untitled) (Research, Society and Development, 2022)
This study aims to present the survey about the production of knowledge from the Law 10.639/03 and its effectiveness in formative practice. Characterized as qualitative research, it was considered the following databases for the collection: Portal de Periódicos Capes, Scielo, Lilacs and Brazilian Digital Library of Theses and Dissertations. As descriptors was adopted the terms "teacher training", "ethno-racial relations", "ethno-racial", "training", "Law 10.639/03" and "physical education", associating the Boolean operator "AND" between the terms. The data collected resulted in 153 scientific productions. After verifying the researches by adopting a selection criteria, they resulted in 02 articles that represented the delimited propositions. Supported by the premise of content analysis, the results indicated the scarcity of scientific production on the theme of ethnic and racial relations in the process of initial formation in Physical Education, showing the inconsistencies between the legality and effectiveness of implementing a curricular policy legitimized in the field of initial formation. The data presented reiterate the need for an expansion in the clarity about the formative constructs as potential influential agents in the initial drafts of the identity of future teachers, from the speed of the effective inclusion of respect and appreciation of ethnic and racial diversity.